Pembinaan Dan Peningkatan Praktek Bacaan Shalat - Harlaeni; Nazaruddin, Andi; Hasmiati (PENDIMAS: Jurnal Pengabdian Masyarakat, 2022)
In this study, it describes the Development and Improvement of Prayer Reading Practices in MI Ar-Rahman, Labuaja Village, Kahu District, Bone Regency. Based on the educational objectives in the National Education System Law Number 22 of 2003, the ultimate goal of Islamic Religious Education is the establishment of Islamic behavior (noble morals) and resignation (faith in Allah) based on Islamic religious instructions (Quran and Hadith). However, along with the development of the times and the era of globalization is increasingly sophisticated which is undeniably making anyone influential with its impact, both negative and positive impacts. Therefore, there needs to be a fortress that can strengthen itself with the influence of globalization. Among them is drawing closer to God. As we know that prayer is the pillar of religion and is a practice that was first worshipped in the hereafter. So it is appropriate that we as Muslims have an obligation to practice and teach this. Therefore, the researcher formulated the problem studied, namely how to provide guidance and commemoration of prayer reading practices for class V and VI students at MI Ar- Rahman As for the purpose of this study, it is to provide guidance and improvement of prayer reading practices to students of grades V and VI in MI Ar-Rahman. This research includes qualitative research with a descriptive type of research with observational data collection techniques for interviews and documentation. The result obtained from this study is the formation of students who understand the practice and prayer readings properly and correctly.